Pengaruh antara Kecerdasan Emosi dan Dukungan Sosial terhadap Stres Kerja pada Anggota Kepolisian Reserse Kriminal di Mabes Polri - Dimas Maulana Pratama. H (Arden Jaya Publisher, 2023)
The phenomenon of work stres of Police Members increases over time, many Police Members are unable to control work stres. Work stres is thought to be due to emotional intelligence and social support. The purpose of this study was to determine the effect between emotional intelligence and social support on work stres in members of the Criminal Investigation at Police Headquarters. This research is a quantitative research using multiple linear regression methods in making decisions about the influence between free varibaels on dependent variables. Sampling in this study used a krejcie table. The results of the study showed the effect between emotional intelligence and social support on work stres in members of the Criminal Investigation at Police Headquarters. The influence is significant but negative. This means that the better the emotional intelligence and social support of police members, the lower the level of work stres.